Analysis of Solar Power Generation System Requirements based on Economic Factors in Photovoltaic Specification Selection - Septian MN, Angga; Nurdiyansah, Reza; Setiawan, Agus; Sunardi, Sunardi (Universitas Negeri Semarang, 2022)
A solar power generation system is a significant investment, and its economic viability is crucial. Analyzing economic factors helps ensure that the selected photovoltaic specifications are cost-efficient, the financial investment is justified, and the energy needs, the project remains sustainable in the long term. It assists stakeholders in making decisions based on economic considerations, energy production and environmental impact. This research aims to analyze the requirements for solar power generation and the selection of photovoltaics based on economic factors. The results of this research explain photovoltaic specifications in terms of efficiency, capacity, technology, and characteristics to understand how they affect the requirements of solar power generation systems. Based on economic factors such as initial investment costs, operational costs, and long-term economic benefits generated. The simulation of the photovoltaic system indicated that photovoltaics with a capacity of 485Wp, using monocrystalline type Canadian Solar HiKu5 Mono PERC, produce the highest output value of 8 kWp using 15 solar panels. It indicates that these specifications offer a high potential for electricity production. The highest economic value amounts to IDR 71,874,000 with an annual yield of 2,920 kWp. The use of monocrystalline photovoltaics is superior and more durable compared to polycrystalline. However, monocrystalline types tend to be more expensive in terms of price. Nevertheless, investment in types can provide long-term benefits in terms of efficiency, durability, and higher electricity production potential despite the higher initial costs. The selection of photovoltaic types should consider these factors, including available budget, desired efficiency, and overall system requirements.